Eksplorasi Bakteri Hidrokarbonoklastik dari Rhizosfer di Lahan Tambang Minyak Rakyat, Kecamatan Babat Toman, Sumatera Selatan - Dwi Hardestyariki; Bambang Yudono; Munawar Munawar (Jurnal Penelitian Sains, 2013)
This study aims to obtain rhizosphere bacteria as a potential agent of bioremediation. The method of sampling the plant rhizosphere by purposive sampling. Soil samples were taken from around the rhizos-phere of plants that live in soil contaminated oil. Bacteria were isolated from the rhizosphere soil samples, then they were selected into steps : performed purification, selection I and selection II. The among bacteria are tested the synergism, then characterized and identified it’s genus. The results showed that there were as many as 34 rhizosphere bacterial isolates were collected from three different sampling locations. Identification of bacteria that have potential as a bioremediation agent. Each bacterial isolate was identified as Sporosarcina sp. A.4.10, Proteus sp. C.6.7, Actinobacillus sp. A.6.3, and Flavobacterium sp. A.5.8.